The electrophilic descriptor (2019)
Through an alternative scheme of representation of energy as a function of the number of electrons, and using the canonical ensemble model, a new electrophilicity descriptor was developed. In our development, we accept the idea that when a system begins to accept electrons from the surroundings, its chemical potential increases, tending to zero when the system is saturated with the maximum amount of charge. In this way, the number of transferred electrons, and therefore the stabilization energy of the system, were modeled by means of a third order approximation which in the state of electronic saturation led to the definition of our electrophilic descriptor. This new reactivity parameter, was tested to reproduce relative electrophilicity tendencies of some chemical systems known for their electrophilic reactivity. Although the results reported here partially demonstrate the potentiality of our descriptor, more systems must be investigated to test the effectiveness of this new reactivity index. © 2019